Implant-specific follow-up imaging of treated intracranial aneurysms: TOF-MRA vs. metal artifact reduced intravenous flat panel computed tomography angiography (FPCTA). Issue 2 (February 2018) - Hänsel, N.H.; Schubert, G.A.; Scholz, B.; Nikoubashman, O.; Othman, A.E.; Wiesmann, M.; Pjontek, R.; Brockmann, M.A.
Abstract : Aim: To compare the diagnostic quality of time-of-flight magnetic resonance angiography (TOF-MRA) and metal-artefact-reduction (MAR) flat-panel-detector computed tomography angiography (FPCTA) and to determine the imaging technique best suited for evaluation endovascular and surgically treated aneurysms. Methods: The image quality of TOF-MRA and MAR-FPCTA of 44 intracranial implants (coiling: n= 20; clipping: n= 15; coiling + stenting: n= 9) in a patient cohort of 25 was evaluated by two independent readers. Images obtained using MAR-FPCTA (20 second scan time, 496 projections, intravenous contrast medium administration; Artis Zee, Siemens Healthcare, Forchheim) were compared with TOF-MRA-images (1.5 or 3 T). Nominal data were analysed using McNemar's chi-square test and ordinal variables using the Wilcoxon rank test. Results: Compared to TOF-MRA, MAR-FPCTA was significantly better suited to detect aneurysm remnants and to evaluate parent vessels after clipping ( p< 0.01). For coil packages >160 mm 3, TOF-MRA provided significantly better assessment than MAR-FPCTA ( p< 0.01). For small coil packages (<160 mm 3 ), no significant difference between TOF-MRA and MAR-FPCTA ( p= 0.232) was observed. For different clip sizes (cut-off 492 mm 3 ) likewise no significant differences were found. The interobserver comparison showed high interrater agreement. Conclusion: MAR-FPCTA is significantly better suited for follow-up examinations of clipped aneurysms, whereas for larger coil packages TOF-MRA is preferable. Smaller coil packages can be analysed using MAR-FPCTA or TOF-MRA. Highlights: Coils and clips impair the quality of CT and Time-of-Flight MR angiography images. Novel techniques like metal artifact reduction (MAR) effectively reduces beam hardening artifacts in flatpanel CTA datasets. We compared the efficacy of MAR-FPCTA and TOF-MRA for imaging cerebrovascular structures in close vincinity to treated cerebral aneurysms. MAR-FPCTA is superior to TOF-MRA for evaluation of parent vessel patency and possible aneurysm remnants in clipped aneurysms.